First presentation of guttate psoriasis triggered by acute tonsillitis - Theocharis Koufakis; Ioannis Gabranis (The Pan African Medical Journal, 2014)

(untitled)
We present a case of a 33 years old man who presented to the Emergency Department of our Hospital with small, red, drop-like lesions located at his arms, legs, torso and back. He had no history of any dermatological disease, but he had a positive maternal family history for plaque psoriasis. The patient had recently recovered from acute tonsillitis after receiving amoxicillin - clavulanic acid therapy. The diagnosis of guttate psoriasis was clinically established, based on the typical presentation and the history of recent upper respiratory infection. He was treated with a combination of oral and topical corticosteroids and he was advised to have frequent follow-up visits to our Dermatology Department. Guttate psoriasis (also known as "Eruptive psoriasis") is more common in young adults and often follows a bacterial or viral infection, but it has also been associated with drugs, stress, skin injury and other trigger factors.